The Impact of Entrepreneurial Leadership, Business Environment, Digital Literacy, and Religiosity on Msme Performance: The Mediating Role of Innovative Behavior in Pekanbaru - Munthe , Richa Afriana; Pratikto , Heri; ., Sudarmiatin; Restuningdiah , Nurika (Journal of Ecohumanism, 2024)
This study examines the influence of entrepreneurial leadership, business environment, digital literacy, and religiosity on the performance of micro, small, and medium enterprises (MSMEs) in Pekanbaru, with innovative behavior as a mediating variable. Using a sample of 300 MSME entrepreneurs and analyzed through Partial Least Squares (PLS) Structural Equation Modeling (SEM), the research finds significant direct effects of entrepreneurial leadership (β = -0.204, p = 0.047), business environment (β = 0.225, p = 0.007), digital literacy (β = 0.139, p = 0.022), and religiosity (β = 0.271, p = 0.011) on business performance. The mediating role of innovative behavior is only significant in the relationship between religiosity and business performance (β = 0.162, p = 0.012). The findings emphasize the critical role of religiosity and innovative behavior in improving MSME performance. This research contributes to the growing literature on MSMEs by demonstrating how leadership, environment, digital skills, and religiosity shape performance outcomes.